Kingdom of Swaziland : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
The fiscal crisis in the Kingdom of Swaziland emanating from a decline in revenue from the Southern African Customs Union and one of the largest public wage bills in sub-Saharan Africa has reached a critical stage. Faced with revenue shortfalls associated with slowing economic activity, uncontrolled public spending, and lack of financing, the authorities continued to deplete central bank reserves and accumulate domestic arrears. The authorities have been able to finance only a minimal amount of expenditure, including wages, utilities, and essential transfers.